Common bunt in organic wheat: unravelling infection characteristics relevant for resistance breeding - Lunzer, Magdalena; Dumalasová, Veronika; Pfatrisch, Kilian; Buerstmayr, Hermann; Grausgruber, Heinrich (Frontiers in Plant Science, 2023)
Common bunt caused by Tilletia tritici and T. laevis has re-emerged as a major threat to wheat yield and quality, especially in organic farming. Resistance against its causal agents is present in the wheat gene pool and provides the most economically efficient and sustainable way to combat the disease since seed treatments approved for organic farming are rare and do not always provide full protection. We tested a winter wheat diversity panel with 128 lines for common bunt resistance in Austria and Czechia, and evaluated the applicability of marker-assisted selection (MAS) via Kompetitive Allele-Specific PCR markers in genotypes with high variation in their genetic background. Field trials were conducted across two years and artificially inoculated with local bunt populations. The virulence patterns of these inocula differed between locations and only 15% of the tested genotypes showed stable resistance across test sites. Number and weight of bunt sori relative to the total number and weight of wheat grains in sampled ears revealed that partial infections of ears were frequently appearing. Forty-two breeding lines harboring combinations of four different resistance QTL were developed through MAS. Out of these, a quarter were resistant with a maximum of 5% common bunt incidence. On the other hand, only six out of 46 tested commercial cultivars and breeding lines showed no infection with common bunt, underlining the present scarcity of bunt-resistant cultivars for organic wheat production. By this study we showed that MAS is a useful tool to speed up the selection of resistant lines even in populations with highly diverse genetic backgrounds, and that it is efficient in pyramiding resistance loci and thereby improving the level of resistance.